2021
DOI: 10.3892/ijmm.2021.5046
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the molecular mechanism of tomentosin‑induced antiproliferative and proapoptotic effects in human multiple myeloma via gene expression profile and genetic interaction network analysis

Abstract: Multiple myeloma (MM) is an aggressive B cell malignancy. Substantial progress has been made in the therapeutic context for patients with MM, however it still represents an incurable disease due to drug resistance and recurrence. development of more effective or synergistic therapeutic approaches undoubtedly represents an unmet clinical need. Tomentosin is a bioactive natural sesquiterpene lactone extracted by various plants with therapeutic properties, including anti-neoplastic effects. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Recently, the antineoplastic activity of SLs has also been evaluated in hematologic tumors such as LB, multiple myeloma (MM), and leukemia cancer cell lines. Virdis et al demonstrated that tomentosin exerts strong antitumor activity on human BL (Raji cell line; [ 52 ]) and MM (RPMI 8226 cell line; [ 53 ]), mediated by inhibition of cell proliferation and induction of apoptosis. Apoptosis was induced by activating both the death receptor and mitochondrial pathways in Raji cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the antineoplastic activity of SLs has also been evaluated in hematologic tumors such as LB, multiple myeloma (MM), and leukemia cancer cell lines. Virdis et al demonstrated that tomentosin exerts strong antitumor activity on human BL (Raji cell line; [ 52 ]) and MM (RPMI 8226 cell line; [ 53 ]), mediated by inhibition of cell proliferation and induction of apoptosis. Apoptosis was induced by activating both the death receptor and mitochondrial pathways in Raji cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, tomentosin causes endoplasmic reticulum stress via upregulation of the ATF4 and DDIT3 genes, suggesting that tomentosin treatment the activation of the protective unfolded protein response signaling might induce cell apoptosis. Functional connection analysis executed by the connectivity map tool indicated that tomentosin acts as the heat shock protein inhibitors on MM cells [ 53 ].…”
Section: Resultsmentioning
confidence: 99%